Locating migration : rescaling cities and migrants - Schiller, Nina Glick; Simsek-Caglar, Ayse (Cornell University Press, 2011)
For the most part, policy discussions of immigrants and the city have been framed by calls for integration and social cohesion (especially in Europe), or they focus on problem areas such as criminality, drugs, poverty, and violence. Migration scholars, meanwhile--whether they are debating assimilation, integration, transnationalism, or diversity--seldom move beyond the framework established by policymakers. Within the migration literature there are many studies of migration to cities and the life of migrants in cities but very little about the relationship of migrants and cities, with cities figuring merely as containers providing spaces in which migrants settle and make a living. This is a book for those concerned with migration as well as with cities.